Is There a Discrepancy? Comparing Enteral Nutrition Documentation With Enteral Pump Volumes. (April 2017) - Musillo, Lisa; Grguric-Smith, Laryssa Marie; Coffield, Edward; Totino, Karen; DiGiacomo, Jody C.
Introduction: Nutrition therapy is essential to the care of critically ill patients. Information that is used to calculate the differences between patients' nutrition prescription and actual provision may be flawed due to errors in manually recording the amount of enteral nutrition (EN) provided. This study's purpose was to evaluate the accuracy of the EN volume delivered as recorded in the electronic medical record (EMR) relative to the EN volume retrieved from the EN pump. Methods: This prospective, blinded, observational study occurred from June 2014 to April 2015 with a total of 218 patients. Patients were identified for the study based on their intensive care unit (ICU) admission and need for EN support. Patients were ICU patients receiving EN support. Results: The major result of this study was that 14% of patients' EN volumes were underdocumented and 26% were overdocumented. Conclusion: These results support the need for a technological platform that directly transmits EN pump volumes in real time to the EMR.